Biocatalysis in polymer chemistry - Loos, Katja (Weinhem : Wiley-VCH Verlag, 2011)
'Biocatalyis in Polymer Chemistry' covers all important aspects in the field, from enzymatic monomer synthesis to polymer modification/degradation.
Includes bibliographical references and index.
Keywords: Polymers -- Biotechnology; Polymers -- Synthesis